A biogeographical regionalization of Australian Acacia species. (15th July 2013) - González‐Orozco, Carlos E.; Laffan, Shawn W.; Knerr, Nunzio; Miller, Joseph T.; Jetz, Walter
Abstract Aim To develop a biogeographical regionalization of Australian Acacia species and to investigate their environmental correlates. Location Australia. Methods We used a previously published framework for delineating biogeographical regions. We calculated species turnover patterns of 1020 Australian Acacia species with distributions estimated from 171, 758 georeferenced herbarium records aggregated to 100 km × 100 km cells (868 across Australia). An agglomerative cluster analysis using a matrix of pairwise Simpson's beta (βsim) dissimilarity values was applied. Eleven environmental variables at the same resolution as the aggregated herbarium records were used to explore the correlates of the βsim patterns using a non‐metric multidimensional scaling (NMDS) analysis. We also used an ANOVA to test the significance of the environmental changes between each pair of biogeographical regions. Results Five major Acacia biogeographical regions were proposed. These bioregions were broadly similar to the biomes of Australia. A new subdivision of the Eremaean biome was proposed for Acacia. The most influential environmental variables for the individual bioregions were: (1) temperature seasonality and topographic flatness for the south‐western temperate bioregion; (2) precipitation during the coldest quarter of the year for the south‐eastern temperate bioregion; (3) annual precipitation, annual mean temperature and precipitation seasonality for the monsoonal bioregion; and (4) percentage of sand in the top 30 cm of the soil, rock grain size, annual mean radiation and annual mean temperature for the Eremaean south and north regions. The NMDS analysis provided support for the observed biogeographical patterns. The statistical test showed a highly significant difference between the environments of the proposed bioregions. Climatic variables were consistent predictors across regions, whereas the influence of soils and topographic features varied among bioregions. Main conclusions The major Acacia biogeographical regions correspond well to historical bioregionalizations, suggesting that the environmental drivers of diversification in Acacia are broadly similar to those that act on the flora as a whole. Climate seasonality combined with annual values and non‐climatic factors provide support for the proposed biogeographical regionalization for Acacia.